The Effectiveness of the Arabic Language Program at Ma'had Al-Jamiah at State Islamic Religious Universities in Aceh - Ana Sofia (Civiliza Publishing, Indonesia., 2026)
Language is the intellectual bloodstream of Islamic higher education. When an Arabic program underperforms, access to classical and contemporary Islamic scholarship is inevitably constrained. This study aims to evaluate the effectiveness of the Arabic language program at Ma’had Al-Jamiah within three Islamic Religious State Universities (PTKIN) in Aceh: UIN Ar-Raniry Banda Aceh, IAIN Lhokseumawe, and IAIN Langsa. This research employs an evaluation design using the Logic Model to examine program components, including inputs, management processes, and results (outputs and outcomes). Data were collected through in-depth interviews, observations, and Focus Group Discussions (FGDs), and were analyzed comprehensively to identify alignment between program planning and implementation. The findings indicate that the Arabic language program has not yet achieved full effectiveness. Significant variations were found among the three Ma’had in terms of resources, managerial practices, and student learning outcomes. These disparities contribute to inconsistencies in both program outputs and long-term outcomes. The study underscores the need for stronger standardization, improved management, and enhanced institutional support to ensure sustainable development of students’ Arabic proficiency and academic competence.